Analisis Yuridis Rekomendasi Bawaslu Tentang Diskualifikasi Petahana (Studi Kasus Pilkada Kabupaten Tasikmalaya Tahun 2020) - Jani, Nur (Law, Development and Justice Review, 2023)
This research was motivated by the polemic on the recommendation of the General Election Supervisory Board (Bawaslu) of Tasikmalaya Regency regarding the disqualification of incumbent Tasikmalaya Regent Candidates who allegedly took advantage of government programs during the 2020 Tasikmalaya Regency Regional Head Election (Pilkada). Meanwhile, the General Election Commission (KPU), which did not implement the recommendations, was decided to have acted according to its authority. Demonstrations were rife everywhere which raised the precariousness of the Pilkada at that time. So, the author's research object is the disqualification recommendation documents which are formally and materially reviewed according to Law Number 10 of 2016 concerning the Election of Governors, Regents, Mayors with qualitative research of the type of retrospective case studies collecting recommendation documents disqualified from Bawaslu, KPU, DKPP, sources of legislation, interviews and the mass media. The results showed that the recommendation for disqualification violated authority in terms of time (onbevoegdheid ratione temporis), so that the Bawaslu was considered unprofessional.